Children around the world full color edition - Baldos, Rick; Rick Baldos (Manila, Philippines Philippine Publishing house, 2021)
Children around the world is a collection of 32 real-life stories of children in their best and worst. From heroic deeds of courage to triumph, these stories will enthrall as well as instruct. In this adventuresome book are timeless truths teen will need growing up
English